Urban kitchen: a form of urban system based on collective operation - Harani, Arnis Rochma; Atmodiwirjo, Paramita; Yatmo, Yandi Andri (Journal of Architecture and Urbanism, 2023)
This paper aims to explore various spatial strategies in urban operations, particularly operation of collective kitchen as a form of the urban system. Through the tracing of micro spatial practice, this paper expands the idea of domestic in urban design discourse. This paper uses a case study method to investigate urban kitchen system in Kampung Bustaman, Semarang, Indonesia, where cooking operations are part of everyday life that is carried out collectively. It shows that the kampung’s everyday operations generate the system of an urban kitchen, where domestic activities shift from the household to become integrated into society, challenging the dualities between domestic and urban space. The mapping of the everyday operations reveals hidden systems of society where connectivity and spatial negotiations play important role. This paper introduces the idea of the urban kitchen as a form of urban system that is transformative, dynamic, and flexible that is driven by collective domestic operations.